ПРИМЕНЕНИЕ ФЕРТИГАЦИИ ДЛЯ ЭФФЕКТИВНОГО ИСПОЛЬЗОВАНИЯ УДОБРЕНИЙ (ОПЫТ ИЗРАИЛЯ) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
This article provides the notion of definition offertigation, fertigation equipment, dosing offertilizers. Benefits offertigation allow are saving labour and cost of equipment, effective (almost 100%) the use of expensive chemical fertilizers. Fertigation is the most efficient and cost-effective way to deliver nutrients to root systems and allows receiving high harvests. Fertigation allows systems management is easily achieved optimal concentrations of fertilizers, their relationship, and these settings can be controlled automatically. The lectures and demonstration materials, given by the organizers of course, were used for writing of the article.